Maltodextrins Based Solid Membranes for the Enantioanalysis of L-Cysteine - Staden, Raluca-Ioana Stefan-van; Holo, Luxolo (Journal of Membrane and Separation Technology, 2014)
Three enantioselective membranes based on maltodextrins with different values of dextrose equivalent (DE) were proposed for the enantioanalysis of L-cysteine. The membranes were used for the design of potentiometric sensors. The slopes of the sensors were near-Nernstian (higher than 58.00mV/decade of concentration) with limits of detection of magnitude order of 10-11 and 10-12 mol/L. The surfaces of the membranes were stable for more than 6 months of continuous use. They can be renewed by polishing on alumina paper.